Deep learning network for NAO robot applications - Leong, Jing Kai (Nanyang Technological University, 2020)
Deep Learning is a subset of machine learning. With deep learning, it is possible to ‘learn’ and make ‘informed choices’ based on the data it has analysed. With the addition of deep learning to eye trackers, it is possible for the device to understand the user’s habits and improve the prediction of the output. In this project, deep learning algorithm is applied to identify rehabilitation exercised performed. The software component will be developed using Pytorch, an open source machine library based on python. For deep learning, a Convolution Neural Network (RNN) is used as it is often used in image classification.